Biochemical changes in relation to larvaldevelopment of the portunid crab Charybdislucifera (Fabricius) - Kannupandi, T; Ravi, A Veera; Soundarapandian, P (Indian Journal of Fisheries, 2011)
All the biochemical constituents in Charybdis lucifera increased with the stagesof development from first zoea to first crab. A total increase of 3.70, 4.76, 3.51,5.92, 4.82, 3.82 and 3.56 folds in dry weight, water, protein, lipid, carbohydrate,chitin, ash and energy respectively were observed during larval development.In general, the maximum rate of accumulation in dry weight and proximatecomposition was found during the transition period between zoeal and megalopalstages. However, the accumulation of carbohydrate was higher during the stagebetween the megalopa and first crab. The fatty acid composition did not showany linear relationship with the stages of larval development. The fatty acidslike 16:0, 18:0, 18:1n-9, 20:4 n-6, 20:5 n-3 and 22:6 n-3 constituted the majorpercentages. The saturated fatty acids showed a minimum of 30.19% in Ist zoeaand a maximum of 38.28% in IIIrd zoea. The monounsaturated fatty acids showeda minimum of 23.49% in Ist zoea and maximum of 33.08% in IInd zoea. Thepolyunsaturated fatty acids showed a maximum of 46.49% in Ist zoea andminimum of 30.29% in IIIrd zoea.